2020
DOI: 10.1021/acsami.0c15991
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Properties of p-Type Bi0.48Sb1.52Te3/Sb2Te3 Composite

Abstract: Constructing a nanocomposite to introduce a coherent interface is an effective way to improve the property of thermoelectric material. Here, a series composites of Bi 0.48 Sb 1.52 Te 3 −x wt % Sb 2 Te 3 (x = 0, 0.3, 0.5, 0.8, and 1.0) were synthesized, where the hydrothermally prepared Sb 2 Te 3 nanosheets were intimately wrapped in the solid-state-reacted Bi 0.48 Sb 1.52 Te 3 matrix. The formation of a coherent interface was observed and confirmed by the scanning electron microscopy characterization. As the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…There are several ways to obtain evidence of the EFE, but confirmation by Pisarenko plots is commonly done. ,, In this study, we adopted the Pisarenko plot based on these previous studies. It is also reported that the increase of the scattering parameter must be confirmed in order to obtain more reliable evidence of the EFE …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several ways to obtain evidence of the EFE, but confirmation by Pisarenko plots is commonly done. ,, In this study, we adopted the Pisarenko plot based on these previous studies. It is also reported that the increase of the scattering parameter must be confirmed in order to obtain more reliable evidence of the EFE …”
Section: Resultsmentioning
confidence: 99%
“…In this study, we focused on improving S thorough the energy filtering effect (EFE). The EFE is applied in composites by forming potential barriers that scatter the charge carriers with lower energy than the potential energy, while the charge carriers with higher energy can contribute to the transport. (CuI) 0.003 Bi 2 Te 2.7 Se 0.3 /Mo, Bi 2 Te 2.7 Se 0.3 /GaAs, (Bi,Sb) 2 (Te,Se) 3 /Te, (Bi,Sb) 2 Te 3 /PbSe, Bi 2 Te 3 /graphene, Bi 0.5 Sb 1.5 Te 3 /Sb 2 O 3 , Bi 0.48 Sb 1.52 Te 3 /Sb 2 Te 3 , and Bi 0.4 Sb 1.6 Te 3 /FeTe 2 are some of the successful examples of the EFE in a Bi 2 Te 3 -based alloy. …”
Section: Introductionmentioning
confidence: 99%
“…dispersed Sb 2 Te 3 into a Bi 0.48 Sb 1.52 Te 3 matrix. [ 128 ] The phase boundaries between the nanoinclusions and the matrix created an effective barrier which improved the PF and increased the effective mass m *. The interface potential barriers can obstruct low‐energy carriers, potentially suppressing the bipolar effect and leading to an obvious increase in carrier mobility, along with a slight decrease in carrier concentration.…”
Section: Discontinuous Interface Modificationmentioning
confidence: 99%
“…Aiming at better mechanical property, Bi 2 Te 3 ‐based polycrystalline bulks were prepared using sintering methods, such as melt spinning, [ 22 ] microwave sintering, [ 23 ] spark plasma sintering, [ 24–27 ] shear/hot extrusion, [ 28–30 ] liquid‐phase pressing, [ 31,32 ] hot pressing/deformation, [ 33–40 ] and so on. For these methods, the temperature gradient is relatively small along the uniaxial direction during the sintering process; the powder particle with low orientation hardly melts, and thus, the sintered product exhibits a weak degree of texture.…”
Section: Introductionmentioning
confidence: 99%
“…However, the zone-melting Bi 2 Te 3 ingots exhibit poor mechanical properties and are easy to cleavage along the basal plane, which seriously limit the reliability of thermoelectric devices, especially the micromodules. [20,21] Aiming at better mechanical property, Bi 2 Te 3 -based polycrystalline bulks were prepared using sintering methods, such as melt spinning, [22] microwave sintering, [23] spark plasma sintering, [24][25][26][27] shear/hot extrusion, [28][29][30] liquid-phase pressing, [31,32] hot pressing/deformation, [33][34][35][36][37][38][39][40] and so on. For these methods, the temperature gradient is relatively small along the uniaxial direction during the sintering process; the powder particle with low orientation hardly melts, and thus, the sintered product exhibits a weak degree of texture.…”
Section: Introductionmentioning
confidence: 99%